The effect of work-family conflict towards turnover intention / Nor Hakimah Mohmad Rahim - Mohmad Rahim, Nor Hakimah (2015)
In response to today's challenging environment on managing work with the advancement of technology and demand will increase the level of stress among employees. Thus, for those who do not manage their stress well will lead to change their job. The main purpose of this correlational research study is to investigate the effect of work-family conflict towards employee's turnover intention and the most significant variable that give effects to turnover intention. The scope of this study focuses on administrative staff in Public Institutions of Higher Learning which is Universiti Teknologi MARA (UiTM) mainly focus on the main campuses in East Coast area. It is hoped to identify whether similar situations are also experienced by UiTM Administrative Staff. In doing so, there are three dimension of work-family conflict being tested namely social support, social network and employee's responsibility. Finally the result shows that all dimensions of work-family conflict have a relationship towards turnover intention. Some recommendations were made with regards to the improvements of the administrative staff to ensure that they would be able to produce higher quality of work and to minimize the feeling of changing to new job.